2022
DOI: 10.25122/jml-2022-0264
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and neonatal outcomes in adolescent and adult patients

Abstract: Preeclampsia is an important health problem with a higher prevalence in the adolescent population. Furthermore, preeclampsia causes adverse maternal and neonatal outcomes. Newborns can be affected by preeclampsia, resulting in lower birth weight or Apgar score, the need for neonatal intensive care, or prematurity. All these complications are also associated with adolescent pregnancies, and together with preeclampsia, it can determine poorer neonatal outcomes. The aim of the study was to compare the neonatal ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“… 30 Another small-scale study yielded the prevalence of preeclampsia in pregnant adolescents as 16.8% 31 while a similar study reported the prevalence as 9.3%. 32 Regardless, the prevalence of preeclampsia was significantly higher in pregnant adolescents than pregnant adults. In this study, the prevalence of preeclampsia was significantly lower in pregnant adolescents and both pregnant adolescents and pregnant adults were statistically similar with respect to the prevalence of preeclampsia (1.3% vs 0.7%, P =.156).…”
Section: Discussionmentioning
confidence: 95%
“… 30 Another small-scale study yielded the prevalence of preeclampsia in pregnant adolescents as 16.8% 31 while a similar study reported the prevalence as 9.3%. 32 Regardless, the prevalence of preeclampsia was significantly higher in pregnant adolescents than pregnant adults. In this study, the prevalence of preeclampsia was significantly lower in pregnant adolescents and both pregnant adolescents and pregnant adults were statistically similar with respect to the prevalence of preeclampsia (1.3% vs 0.7%, P =.156).…”
Section: Discussionmentioning
confidence: 95%
“…Complications of pregnancies include gestational hypertension and GDM. According to the literature, the prevalence of these complications is higher in IVF than in spontaneous pregnancies, with rates of 4.5% vs. 3.6 % for gestational hypertension and 6.6% vs. 4.4% for GDM [ 11 , 31 ]. However, in our study, the prevalence of these complications was much higher, with rates of 18.1% for gestational hypertension and 24.5% for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…It can be diagnosed through routine blood pressure monitoring during prenatal visits [ 4 , 5 ]. In the second half of pregnancy, HBP may be accompanied by proteinuria and may induce adverse neonatal and maternal outcomes in both adolescent and adult women, increasing the risk of preterm birth among adolescents [ 6 , 7 ]. Gestational diabetes is another common second-trimester complication frequently associated with hypertension, especially in overweight women [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%